Inhibition of the mTOR Pathway Exerts Cardioprotective Effects Partly through Autophagy in CLP Rats - Wen Han; Hao Wang; Longxiang Su; Yun Long; Na Cui; Dawei Liu (Hindawi Limited, 2018)
Background. Sepsis-induced myocardial dysfunction is a severe clinical problem. Recent studies have indicated that autophagy and myocardial energy depletion play a major role in myocardial dysfunction during sepsis, a mechanistic target of rapamycin (mTOR) as a master sensor of energy status and autophagy mediator; however, there are little data describing its role during sepsis in the heart. Methods. Cecal ligation and puncture (CLP) or sham operation (SHAM) was performed in rats. After treatment, pathological changes were determined by H&E staining, cardiac functions by echocardiography, the distribution of microtubule-associated protein light chain 3 (LC-3) type II and hypoxia-inducible factor 1α (HIF-1a) by immunohistochemical staining, and autophagic vacuoles by transmission electron microscopy. Moreover, the mTOR signaling pathway and LC3II, p62, and HIF-1a expression were measured by western blotting. Results. Rapamycin alleviated the pathological damage of myocardial tissue, attenuated cardiac dysfunction (left ventricular ejection fraction (LVEF), p<0.05; fractional shortening (FS), p<0.05), and reduced HIF-1a expression (p<0.05). Expectedly, rapamycin decreased the activity of the mTOR pathway in both sham-operated rats (p<0.0001) and CLP rats (p<0.01). Interestingly, we also found inhibition of the mTOR pathway in CLP rats compared with sham-operated rats; phosphorylation of both mTOR (p<0.001) and pS6K1 (p<0.01) was significantly suppressed following CLP challenge. Furthermore, autophagic processes were elevated by CLP; the ratio of LC3II/LC3I (p<0.05) was increased while p62 expression (p<0.001) was decreased significantly; there were also more autophagic vacuoles in CLP rats; and rapamycin could further elevate the autophagic processes compared with CLP rats (LC3II/LC3I, p<0.05; P62, p<0.05). Conclusion. Inhibition of the mTOR pathway has cardioprotective effects on myocardial dysfunction during sepsis induced by CLP, which is partly mediated through autophagy.